Building a pharmacy workforce from the ground up to support the COVID‐19 vaccine rollout: lessons learned and recommendations. - Patanwala, Asad E.; Burke, Rosemary; McNamara, Alexander; Aslani, Parisa; McLachlan, Andrew J. (Journal of Pharmacy Practice & Research, 2022)
The COVID‐19 pandemic has required an unprecedented surge in the pharmacy workforce to support mass vaccination hubs. This review discusses the challenges faced while training and credentialing a surge pharmacy workforce and how these challenges were overcome. The process used for training and credentialing new employees has been described and recommendations and insights have been provided based on the lessons learned at two COVID‐19 mass vaccination hubs in New South Wales. Operationalising one of the largest mass vaccination hubs in Australia required efficient training and credentialing of the pharmacy workforce. This process included the use of pharmacist‐extenders such as students, assistants, and those from other healthcare and non‐healthcare backgrounds. Training was optimised by using a flipped classroom model, so that the vaccine preparation process was provided via asynchronous online videos. The videos covered each step of vaccine dose preparation with visual cues to guide appropriate technique. On‐site training involved use of simulation and checklists for credentialing. Many factors contributed to the success of this process, including the use of triaging and the re‐allocation of personnel based on skill level, collaboration with the Sydney Pharmacy School to train and support a surge workforce involving students, initial on‐site information technology support in the form of pharmacy superusers, the use of checklists and guides for troubleshooting, and assigned pharmacy educators to train new employees. The public health response to the COVID‐19 pandemic forced us to rapidly adapt to build a pharmacy workforce in record time to support mass vaccination hubs. The recommendations and insights provided from our experience can guide future surges. Some of these concepts may also be applied to pharmacy practice in hospitals when resources are constrained.